The voluntary declaration in the tax legislation in UAE: A comparative study - Idelbi, Mona (Journal of Legal Sciences, 2023)
Taxes are the most important public revenues, especially in the context of state intervention and the transformation of the tax from a mere financial tool only into an economic and social guidance tool. Therefore, all countries are keen to preserve this revenue by creating a clear legal system on tax assignment and collection mechanisms, and controlling cases of tax evasion. The tax administration applies several methods to determine the tax base, which differ from one tax to another, and from one tax system to another. The most important of these methods are the tax returns declared by the taxpayers , one of these methods also is to determine the tax base directly by the tax administration. But what about the mistakes which may be appeared in this tax returns? how can the taxpayer correct it to protect himself from the penalties of tax evasion? the tax legislations allowed the correction, and specify the cases in which this correction can be resorted under several names, and show the results of this correction, which differ from one legislation to another, so our research will study those errors contained in the tax returns and the mechanism Processing and correcting it by the taxpayer or the tax administration and its implications, especially in UAE legislation, which devoted a special chapter to this subject under the name of "voluntary declaration" As one of the obligations of the taxpayers, that the taxpayer submits a request to correct his tax returns, requests for tax refunds, or the tax assessment conducted by the Federal Tax Authority, but this was marred by several problems which must be discussed, as its name as a voluntary declaration, , and the dates of its submission which is sometimes unclear, as well as the implications of its submission, which may be inappropriate, in addition to the practical problems that will be resulted to its application , which was raised by the UAE judiciary in many cases.